LA CIUDAD A PUERTA CERRADA. - Duvignaud, Jean (Andamios)
The article focuses on the life and works of sociologist Jean Duvignaud. Topics discussed include his thesis on sociology of theater, launch of a theater magazine by him in 1956, his art and theater projects in France, his works of ephemeral city, its urban planning and existence of patriarchal structures in it.